SUCCESS ANALYSIS OF THE CHAMPION DOOR APPLICATION USING DELONE & MCLEAN SUCCESS MODEL - Isidorus Anung Prabadhi; w Wilonotomo; Abduhafizh Ramadhana (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
The high intensity of immigration data requests is the reason behind the issuance of the Pintu Sijuara application. In line with the implementation of an information system, it is necessary to conduct a post-implementation review. Therefore, this study aims to analyze the success of the application using the Delone & Mclean success model. The sampling technique uses saturated sampling by taking the entire population as the research sample. In the data analysis process, respondents use SPSS as a tool for descriptive statistical analysis and use the PLS-SEM approach with the help of the SmartPLS tool for inferential statistical analysis. By the nine hypotheses, there are three accepted hypotheses: the relationship between service quality and interest in the use, the relationship between interest in the use and net benefits, and user satisfaction with net benefits. The three hypotheses gave positive and significant results as evidenced by the path coefficients and T-Statistics values. Based on the result, "Pintu Si Juara" in Immigration Office Class 1 Special Border Control Surabaya can be said to have good results. However, it can still be developed and improved to be even better by improving in dimensions of service quality that have a significant positive relationship to interest in the use and net benefits